Antimicrobial Susceptibility Profiles of Campylobacter jejuni and Campylobacter coli Isolated from Processed Chickens and Turkeys in Morocco - Zineb Soubai; Nadia Ziyate; Sami Darkaoui; Rim Rais; Siham Fellahi; Benaissa Attarassi; Nabila Auajjar (Poultry)
Monitoring Campylobacter and antimicrobial resistance is critical, as its presence in the food chain, particularly in poultry, represents a serious threat to public health. However, despite its significant impact, this bacterium remains largely underestimated and under-surveilled in many countries, including Morocco. The current study aims to understand the occurrence of Campylobacter spp. in different poultry production systems, highlighting the importance of continuously monitoring antimicrobial susceptibility in these bacteria. For this purpose, 300 poultry samples were collected from a slaughterhouse and 254 from traditional markets in the Rabat-Salé-Kénitra region. The research on Campylobacter was performed according to the standard ISO10272-1(2017), and the confirmation of Campylobacter species was carried out using MALDI-TOF mass spectrometry. Additionally, the disk diffusion method was employed to assess antimicrobial susceptibility, and conventional PCR was utilized to detect the presence of the tet(O) gene in tetracycline-resistant strains. Out of 554 samples collected, 159 (28.7%) tested positive for Campylobacter, of which 84% were identified as Campylobacter coli and 16% as Campylobacter jejuni. Moreover, the results revealed a notably higher detection of Campylobacter in traditional markets (41.33%) than in slaughterhouses (19.85%). Additionally, it was more prevalent in chicken samples (35.37%) than in turkey samples (22.02%). Campylobacter resistance to antimicrobials revealed a resistance rate of 99% to ciprofloxacin, 73% to ampicillin, 82% to tetracycline, 29% to erythromycin, and 0% to gentamicin, as well as to the association of amoxicillin and clavulanic acid. Among the strains with a phenotypic resistance profile to tetracycline, 80% carried the tet(O) gene. The results provide an overview of the current state of antibiotic resistance in Campylobacter in Morocco. They underline the urgent need for the prudent use of antimicrobials and may encourage further research into the development of new antimicrobial agents. They also highlight the importance of raising awareness of the risk of carcass contamination